A 5 cm‐Scale Piezoelectric Jetting Agile Underwater Robot. (27th January 2023) - Li, Kai; Zhou, Xianxin; Liu, Yingxiang; Sun, Jianhua; Tian, Xinqi; Zheng, Haoyuan; Zhang, Lu; Deng, Jie; Liu, Junkao; Chen, Weishan; Zhao, Jie
Abstract : Existing miniature underwater robots, which use electromagnetic actuators or soft actuators, function in shallow waters. However, in the deep sea, the robots face challenges, such as the miniaturization of the pressure protection unit and the driving method for rapid and agile motions. Herein, a jet‐driven method for a high‐pressure underwater environment is proposed by utilizing the high‐frequency vibration of a piezoelectric vibrator. Thereafter, an antihydropressure miniature robot with a body length of less than 5 cm is designed, which can perform the highly agile actions of floating, sinking, hovering, straight driving, and turning under a water pressure of 20 MPa (equal to the pressure under a water depth of 2000 m). A vertical velocity of 2.95 BH/s and a horizontal velocity of 3.22 BL/s are realized by the prototype, and it achieves faster motions than existing miniature underwater robots. Some potential applications have been realized, including small multicorner pipe exploration by carrying a camera, seaweed epidermal cell sampling in designated areas, and large object transportation by swarming, which proves the high maneuverability and agility of the developed robot. These merits make the robot ideal for multitasking operations in narrow environments with high water pressure, such as multiobstacle seabed. Abstract : A 5 cm‐scale agile underwater robot based on the piezoelectric jetting method was proposed. This robot achieves a multi‐locomotion mode under a maximum pressure of 20 MPa, and its maximum speed reaches 3.22 BL/s. The successful exploration of multi‐corner pipes and large object transport by the cooperation of two robots demonstrates the extraordinary ability to work in deep‐sea narrow areas.